Research-Driven Solutions for Enhancing Leadership in Competence-Based Curriculum Implementation in Kenyan Secondary Schools (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: The study adopted a systematic review to analyze AI solutions in enhancing leadership in the implementation of CBC in junior secondary schools in Kenya. The study focuses on challenges relating to inadequate training of teachers, inappropriate resource allocation, and stakeholder engagement. We adopted Technology Acceptance Model (TAM) and Distributed Leadership Theory. The findings reveal that AI may enhance educational leadership by the implementation of real-time monitoring, preparation of teaching resources, and managing the institution more effectively. Moreover, the impeding factors for AI penetration in educational institutions are physical infrastructure, lack of digital literacy, and local conditions. In this regard, the study recommends partnerships between educational institutions and companies manufacturing technology equipment and digital training programs. Further research will focus on the development of specific AI applications to fit the Kenyan educational setup for serving all stakeholders: students, teachers, and school administrators.